Geodetic activities in Latin America and The Caribbean: always IN - Brunini, Claudio Antonio (2012)
Readers may recall that we have published an article” Geodesy: Out with the Old, In with the New” by Prof Chris Rizos in November 2011. We present here some observations of SIRGAS on that article and clarification by Prof. Rizos.